2016
DOI: 10.1155/2016/3487182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Field on Mixed Convection Heat Transfer in a Lid-Driven Square Cavity

Abstract: The effect of magnetic field on fluid flow and heat transfer in two-dimensional square cavity is analyzed numerically. The vertical walls are insulated; the top wall is maintained at cold temperature, Tc while the bottom wall is maintained at hot temperature, Th where Th>Tc. The dimensionless governing equations are solved using finite volume method and SIMPLE algorithm. The streamlines and isotherm plots and the variation of Nusselt numbers on hot and cold walls are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Experimental as well as numerical examination of lid-driven cavity of triangular region when its three sides have different temperature has been discussed by [9] . In addition Bakar et al [10] made analysis of the power of magnetic field in making a difference on the streamlines and contours of the vortices formed in the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental as well as numerical examination of lid-driven cavity of triangular region when its three sides have different temperature has been discussed by [9] . In addition Bakar et al [10] made analysis of the power of magnetic field in making a difference on the streamlines and contours of the vortices formed in the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main divisions of lid-driven cavities. One employs a single-sided moving lid, 30 while the other employs double-or double-sided lid-driven cavities. 31 Kefayati 32 and Taamneh and Bataineh 33 studied the mixed convective heat transfer filled with alumina water as a nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the primary. Very recently Bakar et al [24] studied the effect of magnetic field on fluid flow and heat transfer in a two-dimensional square cavity numerically. The streamlines and isotherm plots and the variation of Nusselt numbers on hot and cold walls were presented.Zahmatkesh and Ardekani [25] analyzed the effect of magnetic field orientation on free convection of several water-based nanofluids in a square porous cavity.…”
Section: Introductionmentioning
confidence: 99%